Pendidikan matematika realistik berbantuan geogebra: Efektifkah ditinjau dari literasi matematika dan kemandirian belajar? - Nurul Indah Septianisha; Syukrul Hamdi; Wahyu Setyaningrum (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2025)
This study aims to 1) describe the effectiveness of implementing RME assisted by GeoGebra in terms of students' mathematical literacy and self-directed learning; 2) describe the effectiveness of implementing PBL in terms of students' mathematical literacy and self-directed learning; and 3) describe the differences in effectiveness between GeoGebra-assisted RME and PBL in terms of mathematical literacy and self-directed learning. This study involved 64 eighth-grade students from a public junior high school in Yogyakarta, utilizing a nonequivalent control group design Data were collected through test and non-test instruments and analyzed using one-sample t-tests and Hotelling's T² test. The findings show that: 1) GeoGebra-assisted RME learning is effective in enhancing both students’ mathematical literacy and self-directed learning; (2) PBL is also proven to be effective in supporting students’ mathematical literacy and self-directed learning; (3) A significant difference exists between the effectiveness of GeoGebra-assisted RME and PBL when viewed from the perspectives of mathematical literacy and self-directed learning; (4) GeoGebra-assisted RME does not outperform PBL in improving mathematical literacy; and (5) GeoGebra-assisted RME is more effective than PBL in promoting students’ self-directed learning. Therefore, the choice of instructional strategy should align with the intended learning outcomes.